INCREASING THE EFFICIENCY OF THE INVESTMENT PROCESS IN MODERN MANAGEMENT CONDITIONS (Multidisciplinary Journal of Science and Technology, 2024)
The article describes the features of the investment policy in the republic, the issues of attracting investments in rail transport, approaches to calculating the cost of cargo mass, cargo losses during transportation, loading and unloading operations.